(untitled) (Fiep Bulletin - online, 2011)
Due to the importance of flexibility in the context of various dance types and due to the lack of scientific studies involving this aspect, the present study aimed to analyze the flexibility in women ballet dancers’ lower members. Ten individuals with ages ranging from 20 and 26 years (21,56 ± 1,94), all of them practicing some kind of dance at least 4 years and with no bones, muscles or joints injuries participated in this study. To value ampleness of hip joint and knee joint it has been used a 360° universal fleximeter, in total circle, Sanny®, made in Brazil. Flexibility degrees has been assessed in the following movements: active hip flexion with knee in flexion, active hip flexion with knees in extension, passive hip flexion with knee in extension, hip extension, hip abduction, hip lateral rotation, hip medial rotation and knee flexion. Three tries have been made in each movement to each volunteer assessed, calculating the average of the tries to be possible establish only one score to each movement. It was observed in results the, excepted in hip medial rotation and knee flexion movements, all the scores could be considered above the ones recommended to health. However, comparing with group used in study submitted to flexibility training program, some scores, mainly about active hip flexion and knee flexion, were considered low. This could evidence flexibility value presented by volunteers might be improved, because they have related to participate occasionally in flexibility trainings.